Single-A-bit dimensionality-adjustable quasi-two-dimensional perovskite material as well as preparation method and application of single-A-bit dimensionality-adjustable quasi-two-dimensional perovskite material

Preparation of quasi-two-dimensional perovskite materials through single A-position design and liquid-liquid mixing method, solving the problems of material stability and preparation process complexity, achieving high-quality and excellent stability of material preparation, and performing in air Good moisture resistance and high resistivity.

CN119145053APending Publication Date: 2024-12-17WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411029711.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Quasi-two-dimensional perovskite materials are susceptible to the influence of humid environment in the air, resulting in oxidation and decomposition, poor stability, and complex preparation process, making it difficult to achieve high-quality large-area preparation.

Method used

Using a single A-position design quasi-two-dimensional perovskite material, the solid-liquid ratio and heating conditions of the precursor solution are controlled by the liquid-liquid mixing method of N-methylpiperazine and lead-containing compounds in hydrobromic acid solution. The continuous adjustable number of inorganic octahedral layers n is achieved, and the preparation process is simplified and the stability is improved.

Benefits of technology

The preparation of quasi-two-dimensional perovskite materials with high quality and excellent stability is achieved, which reduces the complexity of the preparation process, improves the stability and yield of the material, and shows good moisture resistance and high resistance in the air. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145053A_ABST
    Figure CN119145053A_ABST
Patent Text Reader

Abstract

The invention discloses a single-A-bit dimension-adjustable quasi-two-dimensional perovskite material and a preparation method and application thereof, and belongs to the technical field of building materials. The preparation method comprises the following steps: firstly mixing N-methyl piperazine with a hydrobromic acid aqueous solution, acidifying to prepare a solution A, dissolving a lead-containing compound in the hydrobromic acid aqueous solution to prepare a solution B, then mixing the solution A and the solution B, generating a precipitate at room temperature, heating the precipitate until the precipitate is dissolved, preserving heat for 3-5 hours, and finally carrying out crystal growth by using a cooling crystallization method. When the quasi-two-dimensional perovskite crystal is prepared, a cooling crystallization method is adopted, operation is easy, controllability is high, repeatability is good, and meanwhile the crystal prepared through the method is good in transparency, good in stability, small in dark current and capable of being used for X-ray detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of semiconductor materials, and specifically relates to a quasi-two-dimensional perovskite material with a single A site and adjustable dimension, and a preparation method and application thereof. Background Art

[0002] Quasi-two-dimensional (2D) halide perovskite materials have emerged as potential stars for next-generation optoelectronic devices due to their excellent tunability and semiconductor properties, and have therefore developed rapidly in the past decade. The tunability of their properties is closely dependent on the thickness of the quantum well, that is, the number of octahedral layers in each layer (corresponding to the value of n). In addition, the non-centrosymmetric order that organic ligands in quasi-2D halide perovskites may exhibit provides a new perspective and opportunity for in-depth study of the interaction between spontaneous polarization, photovoltaic effect, and carrier transport behavior in electronic and optoelectronic devices.

[0003] Pure 2D and 3D perovskites each have their own advantages, while quasi-2D perovskites, as their heterostructure combination, achieve a balance in performance, providing new possibilities for high-performance optoelectronic devices. Quasi-2D perovskites not only inherit the stability of pure 2D perovskites, but also integrate the high carrier mobility of 3D perovskites, showing excellent performance in the field of photodetectors. However, achieving high photocurrent and effective suppression of dark current remains a challenge, requiring a balance between the high crystallinity and conductivity of the material and defect control.

[0004] From the perspective of materials science, the core challenges facing the field of quasi-2D halide perovskites are how to precisely control the n value in single or polycrystalline materials, and how to establish a close connection between optoelectronic, electronic and ferroelectric properties and structural parameters (such as n value and A-site cations).

[0005] Most of the quasi-two-dimensional perovskites reported so far are of the mixed A-site type, that is, there is a difference between the organic cations supporting the inorganic octahedral framework and the interlayer supporting organic cations. This structural characteristic has a significant impact on the crystal properties and also increases the complexity of the preparation process. Therefore, future research needs to explore how to optimize the structure of this type of material to achieve more outstanding performance.

[0006] In recent years, quasi-two-dimensional perovskite materials have attracted much attention in the field of optoelectronic devices due to their huge application potential. However, this type of material faces many challenges in practical applications. Specifically, quasi-two-dimensional perovskites are easily affected by humid environments in the air, leading to oxidative decomposition, which in turn causes stability problems. This instability greatly limits the long-term stability and reliability of quasi-two-dimensional perovskites in practical devices.

[0007] In addition, the preparation process of high-quality quasi-two-dimensional perovskites is also full of challenges, especially in achieving large-scale preparation. Therefore, the improvement of preparation technology has become an urgent problem to be solved. Summary of the invention

[0008] In view of the technical problems existing in the prior art, the present invention proposes an innovative solution and successfully prepares a quasi-two-dimensional perovskite material with excellent stability, high crystal quality, simple preparation process and high yield. It is worth mentioning that, unlike most reported mixed A-site quasi-two-dimensional perovskites, the quasi-two-dimensional perovskite of the present invention adopts a single A-site design, and its inorganic octahedral layer number n can be continuously adjusted between 1 and 6, providing more possibilities for further optimization of material properties.

[0009] To achieve the above object, the present invention is implemented by the following technical solutions:

[0010] The present invention provides a method for preparing a quasi-two-dimensional perovskite material with a single A site and adjustable dimension, comprising:

[0011] Add N-methylpiperazine to hydrobromic acid solution and acidify to obtain solution A;

[0012] Dissolving the lead-containing compound in a hydrobromic acid solution to obtain a solution B;

[0013] At room temperature, liquid A and liquid B are mixed to prepare a supersaturated precursor solution;

[0014] The supersaturated precursor solution is heated until the precipitate is completely dissolved and kept warm for a period of time;

[0015] The solution after heat preservation is slowly cooled to crystallize, and the crystal growth is continued until it stops.

[0016] Preferably, the molar ratio of N-methylpiperazine to the lead-containing compound is 1:7 to 7:1.

[0017] Preferably, the volume ratio of N-methylpiperazine to hydrobromic acid per 1 g dissolved in liquid A is 1:100 to 1:300.

[0018] Preferably, 3 to 7 ml of hydrobromic acid is used to dissolve 1 g of the lead-containing compound in liquid B.

[0019] In the above scheme, by controlling the solid-liquid ratio of liquid A and liquid B and the molar ratio of N-methylpiperazine and the lead-containing compound, the precursor solution obtained by mixing liquid A and liquid B is a supersaturated solution.

[0020] Preferably, the lead-containing compound is one or more of lead iodide, lead acetate trihydrate or lead oxide.

[0021] Preferably, the supersaturated precursor solution is heated to dissolve at 60-130° C. and kept warm for 3-5 hours.

[0022] Preferably, the cooling rate during crystal growth is 0.5-5° C. / h.

[0023] The present invention also provides a quasi-two-dimensional perovskite material with a single A site and adjustable dimension, wherein the quasi-two-dimensional perovskite material is prepared by the above-mentioned preparation method.

[0024] Preferably, the quasi-two-dimensional perovskite material adopts a single A-site design, and the number of inorganic octahedral layers n is adjustable between 1 and 6.

[0025] The present invention also provides an application of a quasi-two-dimensional perovskite material with a single A site and adjustable dimension in the preparation of an X-ray detection product.

[0026] Compared with the prior art, the technical solution provided by the present invention has the following advantages and beneficial effects:

[0027] In view of the problem that the preparation process of quasi-two-dimensional perovskite is complicated and the crystal stability is poor, the present invention provides a quasi-two-dimensional metal halide perovskite material and preparation method based on organic amine cations. This material not only simplifies the preparation process, but also uses a liquid-liquid preparation method of mixing A and B liquids, which makes the organic amine fully acidified, and also makes the acidified organic amine ion solution more fully contact with the lead-containing compound, reducing the potential barrier of ion migration during the reaction, thereby accelerating the reaction rate and improving the yield. In addition, it also reduces pollution to the environment and shows good stability in the air. After being placed in the air for 30 days, there is no obvious deliquescence and deterioration on the crystal surface. After subsequent testing, there is no obvious change in resistivity.

[0028] Compared with most of the quasi-two-dimensional perovskites reported so far, most of them are mainly based on mixed A sites, and the octahedral skeleton and the organic cations supporting the interlayers are different. The perovskite of the present invention uses N-methylpiperazine to form a single A site design, and by adjusting the ratio between N-methylpiperazine and lead-containing compounds, the number of inorganic octahedral layers n can be continuously adjusted between 1 and 6, providing more possibilities for further optimization of material properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 Actual picture of crystal.

[0030] Figure 2 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 The resistivity of the crystal.

[0031] Figure 3 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 Luminescence spectrum and excitation spectrum of the crystal.

[0032] Figure 4 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 Resistivity of the crystal after being placed in air for 30 days.

[0033] Figure 5 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 The carrier migration lifetime.

[0034] Figure 6 (MPZ)5Pb8Br prepared in Example 4 of the present invention 26 ·H2O crystal physical picture.

[0035] Figure 7 (MPZ)5Pb8Br prepared in Example 4 of the present invention 26 ·XRD of H2O crystals.

[0036] Figure 8 This is a real-object imaging diagram of an X-ray flat-panel detector prepared using the crystal prepared in Example 3 of the present invention.

[0037] Fig. 9 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 Current-time diagram of the crystal under different X-ray doses. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the technical solution of the present invention, the preferred implementation scheme of the present invention is described below in conjunction with specific embodiments, but it should not be understood as limiting the present invention and is only used as an example.

[0039] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0040] The present invention aims to develop a novel quasi-two-dimensional halide perovskite material, which is based on organic amine cations, has a simple and efficient preparation process, and exhibits the characteristics of high resistivity and low dark current, showing great potential in optoelectronic applications such as ray detection.

[0041] The preparation process of the single A-site and dimensionally adjustable quasi-two-dimensional perovskite material is as follows:

[0042] First, a cooling crystallization method is used. This method includes the steps of preparing a precursor solution, heating and dissolving, cooling and crystallizing, and drying. Specifically, N-methylpiperazine is added to a hydrobromic acid solution at room temperature according to the required stoichiometric ratio to prepare liquid A, and the acidification of N-methylpiperazine is achieved. In this process, a large amount of white gas is produced accompanied by heat release. Subsequently, lead bromide is dissolved in a hydrobromic acid solution according to the stoichiometric ratio to obtain liquid B. After liquid A reacts fully, liquid A is mixed with liquid B, and a precipitate will appear at this time. Next, the mixed solution is heated and dissolved until a colorless and transparent solution is obtained. Finally, the temperature is slowly lowered on a cooling hot table until crystals precipitate, and finally a colorless and transparent perovskite crystal is obtained.

[0043] The present invention is further described below with reference to the accompanying drawings and specific implementation examples:

[0044] Example 1

[0045] At room temperature, 222 μL of N-methylpiperazine was added to 1 mL of hydrobromic acid solution to prepare liquid A; at the same time, 0.36 g of lead bromide was dissolved in 2 mL of hydrobromic acid solution to obtain liquid B. After liquid A reacted fully, liquid A and liquid B were mixed at room temperature using a pipette to produce a white precipitate. After the reaction was sufficient, the mixture was heated to 100 ° C and maintained for 3 to 4 hours to completely dissolve the precipitate and form a colorless and transparent solution. After the reaction was completed, the solution was cooled from 100 ° C to 75 ° C on a cooling hot stage at a cooling rate of 1 ° C / h, and finally colorless and transparent crystals were obtained with a yield of 94%. The number of inorganic octahedral layers n was calculated to be 1.

[0046] Example 2

[0047] At room temperature, add 222 μL of N-methylpiperazine to 1 mL of hydrobromic acid solution to prepare liquid A; at the same time, dissolve 1.1 g of lead bromide in 4 mL of hydrobromic acid solution to obtain liquid B. After liquid A reacts fully, use a pipette to mix liquids A and B at room temperature to produce a white precipitate. After the reaction is sufficient, heat to 100 ° C and maintain for 3 to 4 hours to completely dissolve the precipitate to form a colorless and transparent solution. After the reaction is completed, cool the solution from 100 ° C to 75 ° C on a cooling hot stage at a cooling rate of 1 ° C / h, and finally obtain colorless and transparent crystals with a yield of 92%. The number of inorganic octahedral layers n is calculated to be 2.

[0048] Example 3

[0049] At room temperature, add 222 μL of N-methylpiperazine to 1 mL of hydrobromic acid solution to prepare liquid A; at the same time, dissolve 1.1 g of lead bromide in 4 mL of hydrobromic acid solution to obtain liquid B. After liquid A reacts fully, use a pipette to mix liquids A and B at room temperature to produce a white precipitate. After the reaction is sufficient, heat to 100°C and maintain for 3 to 4 hours to completely dissolve the precipitate to form a colorless and transparent solution. After the reaction is completed, cool the solution from 100°C to 75°C on a cooling hot plate at a cooling rate of 1°C / h, and finally obtain colorless and transparent crystals with a yield of 94%. The molecular formula of the crystal is (MPZ)2Pb3Br 10 , it is calculated that the number of its inorganic octahedral layers n is 3.

[0050] Example 4

[0051] At room temperature, add 555 μL of N-methylpiperazine to 2 mL of hydrobromic acid solution to prepare liquid A; at the same time, dissolve 2.936 g of lead bromide in 6 mL of hydrobromic acid solution to obtain liquid B. After liquid A reacts fully, use a pipette to mix liquids A and B at room temperature to produce a white precipitate. After the reaction is sufficient, heat to 100°C and maintain for 3 to 4 hours to completely dissolve the precipitate to form a colorless and transparent solution. After the reaction is completed, cool the solution from 100°C to 75°C on a cooling hot plate at a cooling rate of 1°C / h, and finally obtain colorless and transparent crystals with a yield of 93%. The molecular formula of the crystal is (MPZ)5Pb8Br 26 ·H2O, the number of inorganic octahedral layers n is 4.

[0052] Example 5

[0053] At room temperature, add 222 μL of N-methylpiperazine to 1 mL of hydrobromic acid solution to prepare liquid A; at the same time, dissolve 1.1 g of lead bromide in 4 mL of hydrobromic acid solution to obtain liquid B. After liquid A reacts fully, use a pipette to mix liquids A and B at room temperature to produce a white precipitate. After the reaction is sufficient, heat to 100 ° C and maintain for 3 to 4 hours to completely dissolve the precipitate to form a colorless and transparent solution. After the reaction is completed, cool the solution from 100 ° C to 75 ° C on a cooling hot stage at a cooling rate of 1 ° C / h, and finally obtain colorless and transparent crystals with a yield of 96%. The number of inorganic octahedral layers n is calculated to be 5.

[0054] Example 6

[0055] At room temperature, add 222 μL of N-methylpiperazine to 1 mL of hydrobromic acid solution to prepare liquid A; at the same time, dissolve 1.1 g of lead bromide in 4 mL of hydrobromic acid solution to obtain liquid B. After liquid A reacts fully, use a pipette to mix liquids A and B at room temperature to produce a white precipitate. After the reaction is sufficient, heat to 100 ° C and maintain for 3 to 4 hours to completely dissolve the precipitate to form a colorless and transparent solution. After the reaction is completed, cool the solution from 100 ° C to 75 ° C on a cooling hot stage at a cooling rate of 1 ° C / h, and finally obtain colorless and transparent crystals with a yield of 95%. The number of inorganic octahedral layers n is calculated to be 6.

[0056] The present invention uses Example 3 and Example 4 as preferred cases for product analysis, and other examples have been successfully synthesized and will not be described in detail here.

[0057] Figure 1 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 Actual picture of the crystal. It can be seen from the picture that the crystal has good transparency and has a large size and surface area.

[0058] Figure 2 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 Resistivity of the crystal. As can be seen from the figure: the dark current of the crystal is small, and after calculation, it can be found that its resistivity is large, with an order of magnitude of 11.

[0059] Figure 3 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 The luminescence spectrum and excitation spectrum of the crystal. As can be seen from the figure: the luminescence peak of the crystal in the 350-400nm band appears at around 380nm, and the excitation light wavelength is around 450nm.

[0060] Figure 4 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 Resistivity of the crystal after being placed in the air for 30 days. It can be seen from the figure that the crystal prepared by the present invention has good stability, and the resistivity does not change significantly after being placed in the air for a period of time.

[0061] Figure 5 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 As can be seen from the figure, the carrier migration lifetime of the crystal prepared by the present invention reaches the nanosecond level.

[0062] Figure 6 (MPZ)5Pb8Br prepared in Example 4 of the present invention 26·A real picture of H2O crystals. From the picture, we can see that the crystals are large in size and relatively transparent.

[0063] Figure 7 (MPZ)5Pb8Br prepared in Example 4 of the present invention 26 ·XRD of H2O crystal. From the figure, we can see that the crystal has a tendency to grow preferentially along the (200) crystal plane.

[0064] Application Examples

[0065] The (MPZ)2Pb3Br prepared in Example 3 was integrated by soft pressing. 10 The crystal was prepared into a polycrystalline film, and a direct X-ray flat panel detector was made according to the circuit diagram requirements, and an imaging test was carried out. The test results are as follows Figure 8 .

[0066] Figure 8 The following is a real-life imaging diagram of an X-ray flat panel detector prepared using the crystal of the present invention. It can be seen that the crystal prepared by the present invention has good imaging performance.

[0067] Fig. 9 (MPZ)2Pb3Br prepared in Example 3 of the present invention 10 The current-time diagram of the crystal under different X-ray doses. It can be seen that the crystal prepared by the present invention has a large light-dark ratio and can be used for X-ray detection.

[0068] In summary, the quasi-two-dimensional perovskite crystals of the present invention are prepared by a cooling crystallization method, which is simple to operate, highly controllable, and has good repeatability. At the same time, the crystals prepared by this method have good transparency, good stability, low dark current, and high resistivity, which makes it have broad application prospects in the fields of X-ray detection and so on.

[0069] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a quasi-two-dimensional perovskite material with a single A-site and adjustable dimension. It is characterized in that include: Add N-methylpiperazine to hydrobromic acid solution and acidify to obtain solution A; Dissolving the lead-containing compound in a hydrobromic acid solution to obtain a solution B; At room temperature, liquid A and liquid B are mixed to prepare a supersaturated precursor solution; The supersaturated precursor solution is heated until the precipitate is completely dissolved and kept warm for a period of time; The solution after heat preservation is slowly cooled to crystallize, and the crystal growth is continued until it stops.

2. The method for preparing the single A-site and dimensionally adjustable quasi-two-dimensional perovskite material according to claim 1, It is characterized in that The molar ratio of N-methylpiperazine to the lead-containing compound is 1:7 to 7:

1.

3. The method for preparing the single A-site and dimensionally adjustable quasi-two-dimensional perovskite material according to claim 1, It is characterized in that The volume ratio of N-methylpiperazine to hydrobromic acid in liquid A is 1:100 to 1:

300.

4. The method for preparing the single A-site quasi-two-dimensional perovskite material with adjustable dimension according to claim 1, It is characterized in that 3 to 7 ml of hydrobromic acid are used to dissolve 1 gram of lead-containing compound in liquid B.

5. The method for preparing the single A-site and dimensionally adjustable quasi-two-dimensional perovskite material according to claim 1, It is characterized in that The lead-containing compound is one or more of lead iodide, lead acetate trihydrate or lead oxide.

6. The method for preparing the single A-site quasi-two-dimensional perovskite material with adjustable dimension according to claim 1, It is characterized in that The supersaturated precursor solution is heated to dissolve at 60-130° C. and kept warm for 3-5 hours.

7. The method for preparing a quasi-two-dimensional perovskite material with a single A site and adjustable dimension according to claim 1, It is characterized in that The cooling rate during crystal growth is 0.5 to 5°C / h.

8. A quasi-two-dimensional perovskite material with a single A-site and adjustable dimension, It is characterized in that The quasi-two-dimensional perovskite material is prepared by the preparation method described in any one of claims 1-7.

9. The single A-site and dimensionally adjustable quasi-two-dimensional perovskite material according to claim 8, It is characterized in that The quasi-two-dimensional perovskite material adopts a single A-site design, and the number of inorganic octahedral layers n is adjustable between 1 and 6.

10. Use of the single A-site and dimensionally adjustable quasi-two-dimensional perovskite material as claimed in claim 8 in the preparation of X-ray detection products.